Haplotype variability in mitochondrial rRNA predisposes to metabolic syndrome - Pecina, Petr; Čunátová, Kristýna; Kaplanová, Vilma; Puertas-Frias, Guillermo; Šilhavý, Jan; Tauchmannová, Kateřina; Vrbacký, Marek; Čajka, Tomáš; Gahura, Ondřej; Hlaváčková, Markéta; Stránecký, Viktor; Kmoch, Stanislav; et al. (Communications biology, 2024)
Metabolic syndrome is a growing concern in developed societies and due to its polygenic nature, the genetic component is only slowly being elucidated. Common mitochondrial DNA sequence variants have been associated with symptoms of metabolic syndrome and may, therefore, be relevant players in the genetics of metabolic syndrome. We investigate the effect of mitochondrial sequence variation on the metabolic phenotype in conplastic rat strains with identical nuclear but unique mitochondrial genomes, challenged by high-fat diet. We find that the variation in mitochondrial rRNA sequence represents risk factor in the insulin resistance development, which is associated with diacylglycerols accumulation, induced by tissue-specific reduction of the oxidative capacity. These metabolic perturbations stem from the 12S rRNA sequence variation affecting mitochondrial ribosome assembly and translation. Our work demonstrates that physiological variation in mitochondrial rRNA might represent a relevant underlying factor in the progression of metabolic syndrome.
Keywords: Genetic Predisposition to Disease; Rats; mitochondrie; Metabolic Syndrome; Haplotypes; mužské pohlaví; DNA, Mitochondrial; RNA, Mitochondrial; Diet, High-Fat; dieta s vysokým obsahem tuků; krysa rodu Rattus; RNA mitochondriální; zvířata; metabolický syndrom; mitochondriální DNA; haplotypy; Mitochondria; genetická predispozice k nemoci; inzulinová rezistence; Insulin Resistance; RNA ribozomální; RNA, Ribosomal; Male; Animals